2001
DOI: 10.1128/jvi.75.18.8380-8389.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Middle T-Small T in the Lytic Cycle of Polyomavirus: Control of the Early-to-Late Transcriptional Switch and Viral DNA Replication

Abstract: A comparative analysis of the lytic cycle of wild-type polyomavirus and middle T and small T defective mutants was carried out in the A2 genetic background. The results contrast with those obtained in comparisons between the hr-t type and their middle-T small-T-producing partners as previously described (20). The A2-derived mutants were found to share the maturation defect previously described for the hr-t mutants. However, their defect in DNA replication was more acute, resulting in a 5-to 100-fold decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…Although the activation of late gene expression occurs concomitantly with the amplification of HPV DNA, our study indicates that induction of late gene expression is not strictly dependent upon differentiation-dependent viral DNA amplification. A link between productive replication and late gene expression has been shown for SV40, polyomaviruses, and adenoviruses (8,9,27,31,51,53,54), but it was unclear if similar mechanisms functioned in papillomaviruses. Studies with SV40 have suggested repressors negatively regulate late expression and that replication titrates away these factors, allowing for expression of viral capsid genes (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the activation of late gene expression occurs concomitantly with the amplification of HPV DNA, our study indicates that induction of late gene expression is not strictly dependent upon differentiation-dependent viral DNA amplification. A link between productive replication and late gene expression has been shown for SV40, polyomaviruses, and adenoviruses (8,9,27,31,51,53,54), but it was unclear if similar mechanisms functioned in papillomaviruses. Studies with SV40 have suggested repressors negatively regulate late expression and that replication titrates away these factors, allowing for expression of viral capsid genes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Upon differentiation in suprabasal cells, viral DNA amplification is activated, along with late transcription, leading to virion production (23). A link between productive viral replication and late gene expression has been well documented in other DNA tumor viruses such as simian virus 40 (SV40) (53,54), polyomavirus (8,9,27,31), and adenoviruses (51), but it is not clear if this extends to papillomaviruses.…”
mentioning
confidence: 99%
“…Middle T and small T also play important roles in different aspects of polyomavirus infection (21,23,55). Defects in viral DNA replication and transcription, as well as defects in viral assembly, have been observed in different mutants of middle T and small T (1,7,8,22,38). Each of the viral early proteins also contributes to regulation of host cell function.…”
mentioning
confidence: 99%
“…The repressor activities of transcription factors may participate in the early to late switch of transcription in the lytic cycles of Py and SV40 (49,91): when late gene expression is activated, repressor complexes might be disassociated from transcription factors and replaced by activator complexes containing histone acetyltransferase activities. This might be achieved by titration through replicating viral DNA (49,91,97) or by direct modification of transcription factors or repressor complexes through middle T-and/or small t-mediated signaling (13). Similar control may be exerted upon DNA replication during the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%